Effects of letrozole cotreatment on endocrinology and follicle development in women undergoing ovarian stimulation in an antagonist protocol. Issue 7 (2nd June 2022) - Poulsen, Liv C; Warzecha, Agnieszka K; Bülow, Nathalie S; Bungum, Leif; Macklon, Nicholas S; Yding Andersen, Claus; Skouby, Sven O
Abstract: STUDY QUESTION: What are the downstream endocrine and paracrine consequences of letrozole (LZ) cotreatment during ovarian stimulation and is follicle growth and recruitment affected? SUMMARY ANSWER: Letrozole cotreatment induces marked changes in both the follicular and luteal phase endocrinology causing potentiation of follicle diameter and an improved corpus luteum function without affecting the secondarily recruited follicle cohort. WHAT IS KNOWN ALREADY: Letrozole is a third-generation aromatase inhibitor that is well-established as an effective ovulatory agent, while its possible benefits in standard in vitro fertilization protocols are less thoroughly investigated. STUDY DESIGN, SIZE, DURATION: This study included a double-blinded, placebo-controlled, randomized study with LZ or placebo intervention during ovarian stimulation for IVF treatment, an observational preceding baseline natural cycle and a succeeding follow-up visit. Participants were enrolled between August 2016 and November 2018. Data from the randomized, stimulated cycle were part of a larger RCT, which was previously published. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study was conducted at a public fertility clinic at Herlev Hospital, Denmark, including 31 healthy, normo-responding women eligible for IVF treatment. They underwent a natural baseline cycle and were subsequently randomized to receive either LZ 5 mg (n = 16) or placebo (n = 15) daily during ovarian stimulation from cycle day (CD) 2–3 until induction of ovulation. Throughout both cycles, monitoring was performed every third day with transvaginal ultrasound for assessment of follicle count and diameter, and blood analyses for the determination of twelve endocrine and paracrine parameters. A follow-up assessment was performed at CD2–3 in the succeeding cycle. In the randomized part of the study, we determined differences in blood parameters, follicle recruitment, and follicle diameter. In the observational part of the study, we assessed follicle recruitment in between cycles and its correlation to endocrine parameters. MAIN RESULTS AND THE ROLE OF CHANCE: Letrozole cotreatment significantly suppressed oestradiol (E2 ) concentrations in the follicular phase (area under the curve (AUC) −58% (95% CI [−70%; −43%], P  <   0.001)) and luteal phase (AUC −39% [−63%; −1%], P  =   0.046). This had a marked effect on the endocrine and paracrine output with increased follicular phase luteinizing hormone (AUC +37% [3%; 82%], P  =   0.033), androstenedione (AUC +36% [6%; 74%], P  =   0.016), testosterone (AUC +37% [7%; 73%], P  =   0.013) and 17-OH-progesterone (AUC +114% [10%; 318%], P  =   0.027). Furthermore, follicle-stimulating hormone (FSH) was increased at stimulation day 5 in the LZ group ( P  <   0.05). In the luteal phase, increased corpus luteum output was reflected by elevated progesterone (AUC +44% [1%; 104%], P  =   0.043), inhibin A (AUC +52% [11%; 108%], P  =   0.011), androstenedione (AUC +31% [9%; 58%], P  =   0.006) and testosterone (AUC +29% [6%; 57%], P  =   0.012) in the LZ group. The altered balance between oestrogens and androgens was reflected in a markedly reduced SHBG concentration in the LZ group throughout the luteal phase (AUC −35% [−52%; −11%], P  =   0.009). Endocrine and paracrine parameters were similar between groups at the follow-up visit. Letrozole cotreatment significantly increased the mean number of follicles >16 mm at oocyte retrieval (7.2 vs 5.2, difference: 2.0, 95% CI [0.1; 3.8], P  =   0.036), while the mean total number of follicles at oocyte retrieval was the same (23.7 vs 23.5, difference: 0.2 [−5.8; 6.1], P  =   0.958), and the mean FSH consumption during the stimulated cycle was similar (1500 vs 1520 IU, difference −20 IU [−175; 136], P  =   0.794). Between cycles, the mean antral follicle count at CD2–3 was unchanged (natural cycle 19.0, stimulated cycle 20.9, follow-up cycle 19.7, P  =   0.692) and there was no effect of LZ cotreatment on the recruitment of the next follicle cohort (test for interaction, P  =   0.821). LIMITATIONS, REASONS FOR CAUTION: This study included a relatively small, selected group of healthy women with an expected normal ovarian function and reserve, and the effects of LZ may therefore be different in other patient groups. WIDER IMPLICATIONS OF THE FINDINGS: We confirm some previous findings concerning increased follicle growth and increased endogenous FSH and androgen production, which support the rationale for further studies on the use of LZ cotreatment, for example, as a form of endogenous androgen priming sensitizing the follicle to FSH. Letrozole appears to improve the luteal phase with better stimulation of corpus luteum and progesterone secretion. STUDY FUNDING/COMPETING INTEREST(s): The authors declare no conflicts of interest relating to the present work. TRIAL REGISTRATION NUMBER: NCT02939898.